Evaluation by the Basic Checklist and the risk of 3 years incident long‐term care insurance certification - Kamegaya, Tadahiko; Yamaguchi, Haruyasu; Hayashi, Kunihiko (Journal of general and family medicine, 2017)
Background A rapidly aging society needs effective approaches to support frail older people who have a high risk of requiring long‐term care. We investigated the validity of the Basic Checklist (the “Kihon Checklist”) as a tool to select candidates for a program to prevent long‐term care. Method A survey with questions from the Basic Checklist was conducted with functionally independent older residents aged ≥65 years living in Takasaki City, Japan. Subjects who completed the questionnaire were followed over 3 years for the presence or absence of certification for long‐term care requirement. We used multiple logistic regression analysis to calculate the odds ratio (OR) and 95% confidence interval (95%CI) for long‐term care requirement certification. Results A total of 21 325 subjects were analyzed. The odds ratio was the highest when items number one‐20 had a total of ≥10 checked answers (OR, 2.71; 95%CI, 2.22‐3.32). Physical function (OR, 2.29; 95%CI, 2.05‐2.55), nutritional condition (OR, 1.85; 95%CI, 1.38‐2.48), oral function (OR, 1.40; 95%CI, 1.25‐1.57), whether patients were elected as a care prevention program candidate (OR, 1.90; 95%CI, 1.73‐2.08), Homebound state (OR, 1.91; 95%CI, 1.55‐2.37), the presence of dementia (OR, 1.97; 95%CI, 1.75‐2.20), and depression (OR, 1.96; 95%CI, 1.73‐2.22) were associated with a higher odds ratio. Conclusion Individuals who were selected as long‐term care prevention program candidates based on the Basic Checklist had a higher risk of requiring long‐term care. Older residents who corresponded to 10 or more of the 20 Basic Checklist items are at the highest risk of becoming certified as needing long‐term care.